NEW SOURCES OF THREATS TO THE INVESTMENT SECURITY OF THE BUSINESS SECTOR OF THE NATIONAL ECONOMY OF UKRAINE (Development Service Industry Management, 2023)
The study draws attention to the problems of the state policy of stimulating the development and realization of the economic potential of the entrepreneurial sector of the national economy, but from the standpoint of creating a safe environment for investment activities by business entities. From such positions, the purpose of the study is to identify the latest challenges and threats, as well as to improve the methodological and applied principles of the state policy of countering investment security risks in the entrepreneurial sector of the national economy of Ukraine. It was concluded that the environment of domestic entrepreneurship is characterized by the presence of a number of sufficiently acute threats to the security of the investment process. Such threats have the character of both permanent (systemic) and recent ones, which were actualized during a full-scale war. It has been proven that the state policy for the development of the entrepreneurial sector of the national economy of Ukraine should be aimed at leveling or mitigating the negative impact of identified threats to the investment security of the entrepreneurial sector of the national economy of Ukraine. Despite this, the investment attractiveness of the domestic economy remains low due to the preservation of a whole range of systemic challenges to business investment security. However, in the conditions of the war, these challenges were supplemented by new threats that affect all without exception the stages of the investment process, and, therefore, permeate all links of investment, which critically negatively. In particular, the latest threats in the conditions of a full-scale war relate to: the growth of security (military) risks and the lack of adjustment of their insurance mechanisms (the stage of motivation for investment activity); total uncertainty with terms of war, scale of destruction, reparation mechanisms (planning of investment activity); lack of information about the deregulation of investment processes, which does not promote confidence on the part of global investors (obtaining permits and approvals); loss of control over the fulfillment of contractual obligations within investment agreements, protection of investors' rights (organization and institutionalization of the investment project); lack of institutional reforms, simplification of the regulatory environment for doing business, reduction of corruption risks (state regulation of the investment process); deterioration of the availability of bank loans, withdrawal of foreign investors from the market (investment project financing); the impact of external factors limiting transport and logistics capabilities, lack of energy supply, etc. (development of investments); decrease in incomes of the population and business, narrowing of the domestic market, decrease in profitability and lengthening of payback periods (completion of the investment project, payback of investments).
Keywords: national economy; entrepreneurship; business sector; investment security; new challenges; risks; threats